Strata of the political: epigenetic and microbial imaginaries in post-apartheid Cape Town - Pentecost, M; Cousins, T (Wiley, 2017)
The epigenetic and microbiomic imaginaries that animate public health discourse on perinatal nutrition and the infant gut in South Africa offer a case study through which to reconsider the ontological presuppositions of “space” that frame epigenetic biopolitics. We suggest that the mutual constitution of the relations at stake in and around questions of nutrition, mothers and infants, the gut and sanitation in Khayelitsha, can be understood through a Deleuzian geomorphological image of “strata of the political”. Strata are conjunctural entanglements that temporarily stabilise when distinctions hold briefly, and that bring into alignment particular relations and forces that distribute life and non‐life. This analytic makes visible and available to political life the spatio‐temporal, socio‐natural blurring of categories that epigenetic and microbiomic discourses could afford. Grounded ethnographic descriptions of these processes of “mattering” can challenge political epistemologies and take further critical perspectives on space to open up possibilities for a robust postgenomic politics.